PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA AR PADA MATERI TATA SURYA UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Marinda, Fabila Resti; Wahyuni, Eva Ari; Wulandari, Ana Yuniasti Retno; Hartiningsih, Try; Rakhmawan, Aditya (Natural Science Education Research, 2023)
This study aims to determine improvement of students' critical thinking skills after the application of the AR media assisted discovery learning model to the solar system material for class VII SMP. The research method used in this study is a quasi-experimental research design. The sample selection technique in this study was to use a purposive sampling technique which was carried out at SMP Negeri 1 Kamal in 2022/2023. Analysis of students' critical thinking skills improvement used the N-Gain Score test. The improvement of students' critical thinking skills based on the N-Gain Score test in the experimental class was in the medium category, while in the control class it was in the low category. The conclusion of this study was that application of the discovery learning model assisted by AR media on solar system can make students active in learning and increase students’ critical thinking skills.